Narratives of resistance: femicide and artivist practices in focus (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This essay aims to analyze the case of femicide involving the cycling artist Julieta Hernández in January 2024, from a decolonial feminist perspective aligned with the field of expanded scene in Latin America. It emphasizes the relevance of feminist artivist practices as a means to create counter-narratives to gender violence processes stemming from the colonial/modern system (Segato, 2012). Finally, in light of the concept of liminal practices(Caballero, 2011), the essay explores the construction of performative acts that arise from a fractured social fabric, collectively aiming for the symbolic restoration of identities ruptured by it.
Keywords: femicide; liminal practices; feminist artivism; decolonial feminism